2021
DOI: 10.3390/jcm10163748
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COVID-19 and Non-COVID-19 Pneumonia in Down Syndrome

Abstract: Whether the increased risk for coronavirus disease 2019 (COVID-19) hospitalization and death observed in Down syndrome (DS) are disease specific or also occur in individuals with DS and non-COVID-19 pneumonias is unknown. This retrospective cohort study compared COVID-19 cases in persons with DS hospitalized in Spain reported to the Trisomy 21 Research Society COVID-19 survey (n = 86) with admissions for non-COVID-19 pneumonias from a retrospective clinical database of the Spanish Ministry of Health (n = 2832 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…Asua et al (2021) compared patients with DS and COVID-19 and patients with DS and non-COVID-19 pneumonia. Those authors observed higher in-hospital mortality in patients with COVID-19 and DS (Real de Asua et al 2021 ). Finally, one of the most extensive trials reported that hospitalized patients with DS and positive COVID-19 were more likely to be of advanced age, male, obese, and have diabetes mellitus (Hüls et al 2021 ).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Asua et al (2021) compared patients with DS and COVID-19 and patients with DS and non-COVID-19 pneumonia. Those authors observed higher in-hospital mortality in patients with COVID-19 and DS (Real de Asua et al 2021 ). Finally, one of the most extensive trials reported that hospitalized patients with DS and positive COVID-19 were more likely to be of advanced age, male, obese, and have diabetes mellitus (Hüls et al 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, there are few heterogeneous studies on DS and COVID-19, and because of that, it is difficult to establish the exact risk factors linked to death or high infection rate in patients with DS (Babamahmoodi et al 2020 ; Villani et al 2020 ; Malik and Kathuria 2021 ; Vazquez-Hernández et al 2021 ; Newman et al 2021 ; Vita et al 2021 ; Alsahabi et al 2021 ; Hüls et al 2021 ; Malle et al 2021b ; Illouz et al 2021 ; Clift et al 2021 ; El Kaouini et al 2012 ; Emami et al 2021 ; Real de Asua et al 2021 ; Kuczborska et al 2022 ). For instance, Illouz et al ( 2021 ) observed that patients with DS and COVID-19 were younger and presented lower socioeconomic status; and, curiously, in a recent study, it was demonstrated that the socioeconomic status evaluated by the Human Development Index was associated with a higher case fatality rate in Brazil (Palamim et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High case fatality rate in individuals with Down syndrome and COVID-19 in Brazil: a two-year report Few studies have evaluated the outcomes of COVID-19 in individuals with Down syndrome (DS), which indicated a higher association between DS and longer hospitalisation time, COVID-19 severity and mortality rate. [1][2][3][4][5][6][7][8] From these studies, four out of five have presented a small cohort with less than 40 individuals with DS and COVID-19, [1][2][3][4] except one report that has included 750 individuals. 5 Thus, the real effect of COVID-19 in individuals with DS is not entirely clear, and it would be important to know it, mainly for its importance as a risk factor for death.…”
mentioning
confidence: 99%